Public Health Expenditure and Infant Mortality Rate in Nigeria (International Journal of Scientific Research and Management (IJSRM), 2023)
This study investigated the effect of public health expenditure on infant mortality rate in Nigeria from 2002 to 2021. To achieve the above objective, this study utilized data on infant mortality rate, total government expenditure on health and migration of doctors and nurses trained in Nigeria - doctors and nurses trained in Nigeria but working in other countries from OECD Health Statistics, 2021, WHO, UNICEF, UNFPA, World Bank Group, the United Nations Population Division and Statistical Bulletin of Nigeria’s apex bank. The study employed an Autoregressive Distributed Lag (ARDL) Bounds testing procedure for data analyses. The results revealed that in the long run, total government expenditure on health, as well as migration of doctors and nurses trained in Nigeria - doctors and nurses trained in Nigeria but working in other countries have negative and insignificant relationship with infant mortality rate in Nigeria. However, in the short run, total government expenditure on health, as well as migration of doctors and nurses trained in Nigeria - doctors and nurses trained in Nigeria but working in other countries have positive and significant relationship with infant mortality rate in Nigeria. What this means is that though there has been expenditures on health sector in Nigeria by the government from 2002 to 2021, but the expenditures are low and couldn’t reduce infant mortality rate to a near-zero level in Nigeria. Also, in the short-term, the movement of doctors and nurses from Nigeria to others countries of the world, exacerbated infant mortality rate in Nigeria during the period of study. Based on the forgoing, it is recommended here that government should spend at least 15% of its annual budget on health sector as agreed by African leaders at Abuja in 2015. Government should also reduce the exodus of Nigerian doctors to other countries of the world. This, the government may be able to achieve by increasing budgetary allocation to healthcare sector, enhance doctors’ remuneration, ensure a better work environment with modern healthcare facilities together with general enhancements in basic life facilities including housing, health insurance, security, constant power supply and good roads.